Gut colonization and subsequent infection of neonates caused by extended-spectrum beta-lactamase-producing Escherichia coli and Klebsiella pneumoniae - Jiménez-Rojas, Verónica; Villanueva-García, Dina; Miranda-Vega, Ana Luisa; Aldana-Vergara, Rubén; Aguilar-Rodea, Pamela; López-Marceliano, Beatriz; Reyes-López, Alfonso; Alcántar-Curiel, María Dolores (Frontiers in Cellular and Infection Microbiology, 2024)
The gut microbiota harbors diverse bacteria considered reservoirs for antimicrobial resistance genes. The global emergence of extended-spectrum beta-lactamase (ESBL)-producing Enterobacterales (ESBL-PE) significantly contributes to healthcare-associated infections (HAIs). We investigated the presence of ESBL-producing Escherichia coli (ESBL-PEco) and ESBL-producing Klebsiella pneumoniae (ESBL-PKpn) in neonatal patients’ guts. Furthermore, we identified the factors contributing to the transition towards ESBL-PEco and ESBL-PKpn-associated healthcare-associated infections (HAIs). The study was conducted from August 2019 to February 2020, in a Neonatal Intensive Care Unit of the Hospital Infantil de México Federico Gómez. Rectal samples were obtained upon admission, on a weekly basis for a month, and then biweekly until discharge from the neonatology ward. Clinical data, culture results, and infection information were gathered. We conducted antimicrobial tests, multiplex PCR assay, and pulsed-field gel electrophoresis (PFGE) to determine the antimicrobial resistance profile and genetic relationships. A comparison between the group’s controls and cases was performed using the Wilcoxon and Student t-tests. Of the 61 patients enrolled, 47 were included, and 203 rectal samples were collected, identifying 242 isolates. In 41/47 (87%) patients, colonization was due to ESBL-PEco or ESBL-PKpn. And nine of them developed HAIs (22%, 9/41). ESBL-PEco resistance to cephalosporins ranged from 25.4% to 100%, while ESBL-PKpn resistance varied from 3% to 99%, and both bacteria were susceptible to carbapenems, tigecillin, and colistin. The prevalent blaCTX-M-group-1 gene accounted for 77.2% in ESBL-PEco and 82.2% in ESBL-PKpn, followed by blaTEM 50% and blaOXA-1 43.8% in ESBL-PEco and blaTEM 80.2% and blaSHV 76.2% in ESBL-PKpn. Analysis of clonality revealed identical colonizing and infection isolates in only seven patients. Significant risk factors included hospital stay duration, duration of antibiotic treatment, and invasive device usage. Our findings suggest high ESBL-PEco and ESBL-PKpn rates of colonization often lead to infection in neonates. Attention should be paid to patients with ESBL-PE.